From production to consumption countryside: can the landscape be the new binding of a reshaped community? Example from Alentejo, Southern Portugal - PInto-Correia, Teresa (2013)
The Alentejo landscape is dominated by large scale latifundia managed in an extensive silvo-pastoral system. But in the surrounding area to all small towns, small scale farming dominates, with olive groves combined with pastures, fruit orchards, and vegetable gardens, in the most fertile and water abundant soils. These small scale farm units have increasingly lost their importance as production units over the last decades, but farming has in many of them been maintained, by the ageing farmers. In the meantime, these small farms became extremely attractive for new comers, who settle in the rural context as lifestyle farmers, or simply as new residents (permanent or week-end houses). These new comers have higher economic possibilities, often rebuilding the houses and investing in the land. Along with new investment capacities, they also have new demands. They may be able to keep farming, but lack the traditional knowledge and have other production models. Is the farm system which has produced the attractive landscape progressively disappearing – or changing - according to a renewed lifestyle production? The social pattern changes, where traditional local families are neighbor to new-comers from Lisbon, or foreigners. One main issue is whether these new owners have the capacity and the will to keep up the traditional farm system which created the landscape they were attracted to, and who can be responsible for the required work. But mainly, which new binding factors can be connecting this reshaped community, once the local farmers, now mostly aged, will disappear, and who can represent this community. And how the existing institutional arrangements can cope with the new social and land use patterns. The paper presents a case-study in Montemor-o-Novo, a small town 100 km from Lisbon, and thus highly subject to the pressure from urban users. The transition theory conceptual framework has been applied to study changes in owner consumption patterns, in land use and in farming practices. The paper i) characterizes broadly this larger phenomenon composed of individual changes and identifies the new ways in which rural landscapes are consumed, ii) explores how this rural area may be shaped by it at the level of social relationships and landscape, and iii) discusses its potential contribution to the sustainability of small scale agriculture in the region of Alentejo.